2007
DOI: 10.1007/s11113-007-9040-y
|View full text |Cite
|
Sign up to set email alerts
|

An Explanatory Model for Projecting Regional Fertility Differences in the Netherlands

Abstract: Current differences in the level of the total fertility rate (TFR) between Dutch municipalities are smaller than they were in the 1970s and 1980s. Nevertheless, there are still considerable differences. Small municipalities have higher TFRs than large cities. This article aims to answer the question whether these differences will decline further until differences between large and small cities disappear. For that purpose we develop a regression model of regional differences in the TFR including demographic, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 22 publications
3
38
0
2
Order By: Relevance
“…The results obtained in this study are similar to those observed in studies conducted in other countries [15,18,30,31,32,33], despite the disparate methods used to estimate them. Analysis of changes in the patterns of reproductive behaviour during the period of 1995-2014 indicated a similar shift in the age of highest fertility, from 20-24 to 25-29 years, both in rural and urban areas; but in rural areas this process proceeded with several years of delay compare to urban areas.…”
Section: Limitations and Strengthssupporting
confidence: 88%
“…The results obtained in this study are similar to those observed in studies conducted in other countries [15,18,30,31,32,33], despite the disparate methods used to estimate them. Analysis of changes in the patterns of reproductive behaviour during the period of 1995-2014 indicated a similar shift in the age of highest fertility, from 20-24 to 25-29 years, both in rural and urban areas; but in rural areas this process proceeded with several years of delay compare to urban areas.…”
Section: Limitations and Strengthssupporting
confidence: 88%
“…Lesthaeghe & Neidert, ; Rotariu, ). However, there is relatively little published research comparing specific countries and examining the subnational, regional spatial dispersion of the SDT and spatial variation of reproductive behaviour within countries (De Beer & Deerenberg, ). Compton () attributed this to a less obvious relationship between fertility and geographical space compared with migration and mortality, where differentials may respectively be associated with uneven economic development and variable environmental conditions.…”
Section: Second Demographic Transition and Fertility Differences In Ementioning
confidence: 99%
“…De Beer and Deerenberg () note that because subnational fertility trends are important for projection purposes, without having an explanation for the regional differences, it is difficult to decide whether changes observed in the past are likely to continue in the future and, if so, to what extent. Although this analysis could not disentangle whether other migration theories such as socialization, adaptation, and disruption are involved in explaining regional differences, we have shown that composition factors and place are both important for explaining fertility progression.…”
Section: Discussionmentioning
confidence: 99%